A global synthesis of fire effects on pollinators. Issue 10 (13th June 2019) - Carbone, Lucas M.; Tavella, Julia; Pausas, Juli G.; Aguilar, Ramiro
Abstract: Aim: Understanding fire effects on pollinators is critical in the context of fire regime changes and the global pollination crisis. Through a systematic and quantitative review of the literature, we provide the first global assessment of pollinator responses to fire. We hypothesize that pollinators increase after fire and during the early postfire succession stages; however, high fire frequency has the opposite effect, decreasing pollinators. Location: Terrestrial ecosystems, excluding Antarctica. Time period: Data collected from 1973 to 2017. Major taxa studied: Insects (Coleoptera, Diptera, Hymenoptera and Lepidoptera) and a few bird species. Methods: We first compiled available studies across the globe that assessed fire effects on pollinator communities. Then, by means of hierarchical meta‐analyses, we evaluated how different fire regime parameters (fire frequency, postfire time and fire type) and habitat characteristics affect the abundance and richness of animals that act as pollinators. We also explored to what extent the responses vary among taxa groups and life history traits of pollinators (sociality system, nest location and feeding specialization), and among biomes. Results: The overall effect size of fire on pollinator abundance and richness across all studies was positive. Fire effect was especially clear and significant in early postfire communities, after wildfires, and for Hymenoptera. Taxonomic resolution influenced fire effects, where only studies at the species/genus and family levels showed significant effects. The main exceptions were recurrent fires that showed a negative effect, and especially wildfire effects on Lepidoptera abundance that showed a significant negative response. Main conclusions: Pollinators tend to be promoted after a wildfire event. However, short fire intervals may threat pollinators, and especially lepidopterans. Given the current fire regime changes at the global scale, it is imperative to monitor postfire pollinators across many ecosystems, as our results suggest that fire regime is critical in determining the dynamics of pollinator communities.